2011
DOI: 10.1016/j.crohns.2011.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Emigration to western industrialized countries: A risk factor for developing inflammatory bowel disease

Abstract: People who emigrate to westernised countries have a higher risk for developing IBD, especially UC. Environmental factors related with industrialization seem to play an important role in the pathogenesis of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 15 publications
1
54
0
1
Order By: Relevance
“…The rapid pace of these epidemiological changes is too brisk for them to result from changes in gene frequency, pointing to an environmental effect on the risk of disease. Studies of emigrant groups support this hypothesis [7]. Studies of migrant populations suggest early childhood environmental influence is crucial; children take on the risk profile of their new environment, whereas their parents maintain the risk profile of their country of origin [11].…”
Section: The Gut Microbiota: the Proximate Environmental Risk Factor mentioning
confidence: 57%
See 1 more Smart Citation
“…The rapid pace of these epidemiological changes is too brisk for them to result from changes in gene frequency, pointing to an environmental effect on the risk of disease. Studies of emigrant groups support this hypothesis [7]. Studies of migrant populations suggest early childhood environmental influence is crucial; children take on the risk profile of their new environment, whereas their parents maintain the risk profile of their country of origin [11].…”
Section: The Gut Microbiota: the Proximate Environmental Risk Factor mentioning
confidence: 57%
“…The increasing prevalence of IBD worldwide also supports the primacy of environmental risk factors [7,8] in the development of IBD, except in rare cases of monogenic disease [9]. The most consistent epidemiological feature of both UC and CD is the increase in incidence and prevalence when a society transitions from developing to developed [10].…”
Section: The Gut Microbiota: the Proximate Environmental Risk Factor mentioning
confidence: 96%
“…Such work was done on the occurrence of cancer in migrants in the 1990s in Uruguay (48) , Brazil (9) and Argentina (30) . An interesting recent Spanish study on emigration looked at 34 patients who had emigrated to other parts of Europe and 16 to South America (6) . The authors suggested that emigration was associated with ulcerative colitis and not with Crohn's disease.…”
Section: Incidence and Prevalence In Central And South Americamentioning
confidence: 99%
“…Air pollution and in particular burning fossil-fuels related pollutants which contains a large amount of nitrogen oxides and levitate particles have been problematic in recent decades especially in urban and industrial communities as a public health hazard [10,[15][16][17][18][19]. In fact the risk factors of industrialization were not fully evaluated and in this retrospective study, we have evaluated any potential effect of air pollution as a trigger factor on the rate and duration of hospital admission due to hepatic encephalopathy among a referral center in a capital industrial city of Khuzestan province.…”
Section: Introductionmentioning
confidence: 99%